Intravenous injection of a novel viral immunotherapy encoding human interleukin-7 in nonhuman primates is safe and increases absolute lymphocyte count - Charles-Antoine Coupet; Clarisse Dubois; Alexeï Evlachev; Nadine Kehrer; Marie Baldazza; Sam Hofman; Michel Vierboom; Perrine Martin; Geneviève Inchauspe (Taylor & Francis Group, 2022)
Persistence of an immunosuppression, affecting both the innate and adaptive arms of the immune system, plays a role in sepsis patients' morbidity and late mortality pointing to the need for broad and effective immune interventions. MVA-hIL-7-Fc is a non-replicative recombinant Modified Vaccinia virus Ankara encoding the human interleukin-7 fused to human IgG2 Fc fragment. We have shown in murine sepsis models the capacity of this new virotherapy to stimulate both arms of the immune system and increase survival. Herein, an exploratory study in nonhuman primates was performed following a single intravenous injection of the MVA-hIL-7-Fc used at the clinical dose to assess its safety and biological activities. Four cynomolgus macaques were followed for 3 weeks post-injection (p.i), without observed acute adverse reactions. Circulating hIL-7-Fc was detected during the first 3-5 days p.i with a detection peaking at 12 h p.i. IL-7 receptor engagement and downstream signal transduction were detected in T cells demonstrating functionality of the expressed IL-7. Expansion of blood lymphocytes, mainly CD4 and CD8 naïve and central memory T cells, was observed on day 7 p.i. together with a transient increase of Ki67 expression on T lymphocytes. In addition, we observed an increase in circulating B and NK cells as well as monocytes were albeit with different kinetics and levels. This study indicates that a vectorized IL-7-Fc, injected by intravenous route at a relevant clinical dose in a large animal model, is active without adverse reactions supporting the clinical development of this novel virotherapy for treatment of sepsis patients.